2012
DOI: 10.1109/tps.2012.2196029
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Homogeneous Atmospheric-Pressure Dielectric Barrier Discharge in a Large-Gap Argon Gas

Abstract: The generation of homogeneous dielectric barrier discharge (DBD) in a 8-mm large-gap Ar at atmospheric pressure by employing a microsecond pulsed power supply excitation is presented. The electrical and optical characteristics of the homogeneous DBD are experimentally studied, and the comparison of the discharge characteristics with its sinusoidal counterpart and the improvement of the discharge stability using the water electrodes are also experimentally investigated. Results show that, as compared with filam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The voltage pulses, with a 2.5 kV amplitude, have a duration of 245 ns and a rising time of 45 ns. Two distinct current discharges, with durations of 40 and 70 ns, are produced at the rising and falling edges of each voltage pulse, respectively. The smooth curves of the current pulses indicate that two diffuse and homogeneous ultrashort discharges are produced for each period. ,, Such homogeneous discharges are particularly suitable for the treatment of fragile substrates such as polymer textiles. The voltage pulses, with a constant duration of 245 ns, were repeated with frequencies ranging from 50 Hz to 10 000 Hz (see Table S1 in the Supporting Information), allowing to investigate t off from 0.1 to 20 ms and duty cycles (DC) from 0.001% to 0.2%.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…The voltage pulses, with a 2.5 kV amplitude, have a duration of 245 ns and a rising time of 45 ns. Two distinct current discharges, with durations of 40 and 70 ns, are produced at the rising and falling edges of each voltage pulse, respectively. The smooth curves of the current pulses indicate that two diffuse and homogeneous ultrashort discharges are produced for each period. ,, Such homogeneous discharges are particularly suitable for the treatment of fragile substrates such as polymer textiles. The voltage pulses, with a constant duration of 245 ns, were repeated with frequencies ranging from 50 Hz to 10 000 Hz (see Table S1 in the Supporting Information), allowing to investigate t off from 0.1 to 20 ms and duty cycles (DC) from 0.001% to 0.2%.…”
mentioning
confidence: 95%
“…To minimize the effect of the plasma on the monomer dissociation, PECVD can operate in the pulsed mode, where the plasma alternates on ( t on ) and off periods ( t off ). ,, It has been shown, from low-pressure works, that reducing the pulses duration from milli- to microseconds can improve the structural retention of monomers and preserve its functional groups. , Recently, studies have indicated that homogeneous dielectric barrier discharge (DBD) can easily be generated at atmospheric pressure using micro- or nanopulsed DC power supply. , Ultrashort square-pulsed DBD have been shown suitable for the treatment of various surfaces and have been investigated to promote hydrophobicity with organic–inorganic hybrid coatings and to deposit dense inorganic silicon oxides thin films. , Nevertheless, in comparison to chopped AC AP-DBD, atmospheric pressure nanosecond square-pulsed DBD has never been investigated for the deposition of organic and polymer coatings. It is well-known that different mechanisms occur during t on and t off in chopped AC AP-DBD .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a dielectric in a plasma reactor allows to obtain barrier discharges (DBD) and prevents arcing and increasing the local temperature resulting from decreased concentration and ozone generation efficiency. There are many factors that affect the operation of the reactor; supply voltage [1], type of gas used [2], electrode geometry [3], discharge gap and type of dielectric [4][5][6]. The manuscript presents the results of experimental studies on the effect of electrode geometry on ozone concentrations.…”
Section: Introductionmentioning
confidence: 99%